2015
DOI: 10.1136/annrheumdis-2015-eular.1709
|View full text |Cite
|
Sign up to set email alerts
|

OP0100-HPR Does Self-Report of Foot Problems Agree with Clinical Examination in People with Rheumatoid Arthritis?

Abstract: BackgroundData about the frequency of foot problems in rheumatoid arthritis (RA) can be obtained through self-report or clinical examination. The level of agreement between these two approaches has not been established in RA.ObjectivesTo measure levels of agreement between self-report and clinical examination of foot problems in RA.MethodsA random sample of RA patients who had self-reported foot problems in a questionnaire underwent a structured foot examination and clinical interview conducted by a single obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Equally, self-reporting may unreliable owing to an incorrect ‘self-diagnosis’. However, a recent study reported high levels of agreement between self-rpert and clinical examination for straight foward foot complaints in people with rheumatoid arthritis [ 39 ]. It is difficult to exclude the possibility of a responder bias; i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Equally, self-reporting may unreliable owing to an incorrect ‘self-diagnosis’. However, a recent study reported high levels of agreement between self-rpert and clinical examination for straight foward foot complaints in people with rheumatoid arthritis [ 39 ]. It is difficult to exclude the possibility of a responder bias; i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Our work was based on self-reported symptoms and selfreport questionnaires are limited due to recall bias. However, high levels of agreement between self-reported foot complaints and clinical examination have been reported in rheumatoid arthritis [39]. Moreover, the literature frequently highlights differences between patient perception and impact of symptoms and clinical assessment/categorisation [40][41][42].…”
Section: Discussionmentioning
confidence: 99%